2021
DOI: 10.1111/trf.16759
|View full text |Cite
|
Sign up to set email alerts
|

Background rate of low‐level HCV RNA in anti‐HCV confirmed‐positive and minipool nucleic acid test‐nonreactive blood donations

Abstract: Background In 2019, the Food and Drug Administration revised the requirement for further testing of anti‐HCV‐reactive donations testing nucleic acid (NAT)‐nonreactive via routine mini‐pool (MP)‐NAT. Individual donation (ID)‐HCV NAT was required as a supplemental test prior to a second FDA‐licensed anti‐HCV assay; if ID‐HCV‐NAT is reactive, no further testing is required. This study investigated the rate of low‐level RNA in anti‐HCV‐reactive donation samples prior to and following the implementation of suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…12 Surveillance data from repeat donations for 2019 published by the Robert Koch-institute (RKI) and the look-back data from 2008-2015 reported to the Paul-Ehrlich-Institut (PEI) 8 justified due to the marginal effect on the RR of TT HCV infection compared to applied MP-NAT test strategies. 7,8,23 The outcome of the recent nationwide survey indicates that the implemented donor screening strategies are sufficient to ensure a high standard of blood safety in Germany. 8 Due to the high doubling-time of HCV in the early period of infection, most countries in the world with a low HCV prevalence, like Western Europe, have implemented HCV NAT based on the MP strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Surveillance data from repeat donations for 2019 published by the Robert Koch-institute (RKI) and the look-back data from 2008-2015 reported to the Paul-Ehrlich-Institut (PEI) 8 justified due to the marginal effect on the RR of TT HCV infection compared to applied MP-NAT test strategies. 7,8,23 The outcome of the recent nationwide survey indicates that the implemented donor screening strategies are sufficient to ensure a high standard of blood safety in Germany. 8 Due to the high doubling-time of HCV in the early period of infection, most countries in the world with a low HCV prevalence, like Western Europe, have implemented HCV NAT based on the MP strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is important to note that most blood donations in Germany (more than 70%) screen for HCV RNA by MP96‐NAT. Although ID‐NAT testing would have prevented the recent HCV transmission, its introduction does not seem to be justified due to the marginal effect on the RR of TT HCV infection compared to applied MP‐NAT test strategies 7,8,23 . The outcome of the recent nationwide survey indicates that the implemented donor screening strategies are sufficient to ensure a high standard of blood safety in Germany 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Cappy et al 20 estimated that approximately 0.5% of HCV‐antibody positive but NAT negative blood donations in France had low HCV RNA levels. Groves et al 21 reported that low‐level HCV‐RNA reactivity is decreasing over time from 0.34% to 0.1%, perhaps due to the widespread use of highly effective direct‐acting antiviral treatments of HCV infection in USA.…”
Section: Discussionmentioning
confidence: 99%
“…The chronic hepatitis B virus infection are also health problems in Iraq. The reported prevalence of hepatitis B rate is (2-4) % among normal Iraqi population which is among the countries of intermediate hepatitis B endemicity [7]. Countries with intermediate or high endemicity must have mass immunization for all infants at birth and for all risk groups [8].…”
Section: Introductionmentioning
confidence: 99%